Time-averaged height distribution of the Kardar–Parisi–Zhang interface. (30th May 2019) - Smith, Naftali R; Meerson, Baruch; Vilenkin, Arkady
Abstract: We study the complete probability distribution of the time-averaged height at point x   =  0 of an evolving 1  +  1 dimensional Kardar–Parisi–Zhang (KPZ) interface . We focus on short times and flat initial condition and employ the optimal fluctuation method to determine the variance and the third cumulant of the distribution, as well as the asymmetric stretched-exponential tails. The tails scale as and, similarly to the previously determined tails of the one-point KPZ height statistics at specified time . The optimal interface histories, dominating these tails, are markedly different. Remarkably, the optimal history, , of the interface height at x   =  0 is a non-monotonic function of time: the maximum (or minimum) interface height is achieved at an intermediate time. We also address a more general problem of determining the probability density of observing a given height history of the KPZ interface at point x   =  0.